Exploring Service Science : 10th International Conference, IESS 2020, Porto, Portugal, February 5–7, 2020, Proceedings /: 10th International Conference, IESS 2020, Porto, Portugal, February 5–7, 2020, Proceedings. (2020) - Unknown
No abstract available